1998
DOI: 10.1038/sj.sc.3100701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heterotopic ossification of the hip on bone densitometry: a study in spinal cord injured patients

Abstract: Objective: To evaluate (1) the magnitude of falsely elevated bone density results caused by heterotopic ossi®cation (HO) around the hip and (2) e ect of age of patients when the measurement was taken, age of patients at injury, and age of injury (time since event) to the prevalence of HO. Subjects and methods: We blindly analyzed plain radiographs of the hip [(obtained within 1 month of dual energy X-ray absorptiometry (DEXA)] in 107 spinal cord injured (SCI) patients for HO and matched the result to the three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…As bone complications, for example, heterotopic ossification, scoliosis, osteomyelitis, arthroses, internal fixation of bone, can influence DEXA precision, 28,29 International Society for Clinical Densitometry (ISCD) scan artefact criteria were applied and scans were extracted accordingly (periarticular hip artefact n ¼ 5, two FES, three CON). Percentage change (%) BMD was derived from baseline BMD (g/cm 2 ) and % fat mass (FM) from total body mass (g).…”
Section: Analysesmentioning
confidence: 99%
“…As bone complications, for example, heterotopic ossification, scoliosis, osteomyelitis, arthroses, internal fixation of bone, can influence DEXA precision, 28,29 International Society for Clinical Densitometry (ISCD) scan artefact criteria were applied and scans were extracted accordingly (periarticular hip artefact n ¼ 5, two FES, three CON). Percentage change (%) BMD was derived from baseline BMD (g/cm 2 ) and % fat mass (FM) from total body mass (g).…”
Section: Analysesmentioning
confidence: 99%
“…In spinal cord injured patients, disuse osteoporosis is frequently observed below the level of SCI, and this is more pronounced at the hip. 49 Microfractures of subchondral bone occur in osteoporosis, which is more likely in states of diminished sensibility in particular if there is increased exposure to trauma. 43 Such microfractures could lead to cell death, and the subsequent subarticular collapse of the femoral head.…”
Section: Discussionmentioning
confidence: 99%
“…That was why we conducted this study using substantial numbers of patients to determine the magnitude of in¯uence of HO on results, and found that HO can cause false elevation ranging from 29 ± 101% for bone mineral content (BMC), 21% for bone mineral density (BMD), and 39 ± 43% for percentage of BMD compared to age-matched controls. 1 The second explanation is criteria of`clinically obvious HO' used in our study. The clinically obvious HO has to do with subjects having fracture before, or they had been noticed due to debridement, or deformities in the hip that indicated HO was present.…”
Section: In Reply To Dr Papadaki and Colleaguesmentioning
confidence: 99%
“…With regards to the letter from Dr Papdaki and colleagues concerning our article, 1 we would like to address certain points.…”
Section: In Reply To Dr Papadaki and Colleaguesmentioning
confidence: 99%